Biodegradable properties of AZ31-0.5Ca magnesium alloy. (15th October 2022) - Masood Chaudry, Umer; Farooq, Ameeq; Malik, Abdul; Nabeel, Muhammad; Sufyan, Muhammad; Tayyeb, Asima; Asif, Sumbal; Inam, Aqil; Elbalaawy, Ahmed; Hafez, Eslam; Jun, Tea-Sung; Hamad, Kotiba
ABSTRACT: In this work, the effect of Ca addition on the microstructure, mechanical properties, electrochemical corrosion and biocompatibility of AZ31 Mg alloy was investigated. Scanning electron microscopy and electron probe microanalyzer were used to analyse microstructural characteristics of both alloys. Open circuit potential, potentiodynamic polarisation and electrochemical impedance spectroscopy techniques were carried out in Ringer lactate solution at 37 ± 1°C to determine the mechanism of corrosion and rate of deterioration of AZ31 and AZ31-0.5Ca. The results revealed that addition of Ca significantly enhanced the corrosion resistance of AZ31 (20.21 mpy and 10.08 mpy for AZ31 and AZ31-0.5Ca, respectively), which was attributed to the presence of second phase particles. the cell viability and biocompatibility of the both alloys were determined by performing the cytotoxicity test after 24 h, 48 h and 72 h incubation in L929 and MC3T3-E1 cell extract. Both the alloys demonstrated adequate cell viability and biocompatibility. Graphical abstract: uf0001